Development of an Android based information system for VELOX nano-satellite - Tay, Shao Jie (2015)
This Final Year Project (FYP) is based on the predecessor’s work titled “Development of A Web-Based Ground Station System for an Advanced Nano-Satellite (Velox-I)” This project is an adaptation of the web-based ground station system into a subsidiary companion android app. The aim of the FYP is to create a companion Android Application (app) so as to act as a quick reference for researchers and staff on the move. The app should be able to have features such as user login to ensure security and confidentiality, basic information lookup or viewing, image gallery to view images on the go, and last but not least, directing the users to the official Satellite Research Centre (SaRC) website should they require more information. With the world today gradually moving away from the Internet to the Mobile device, it is only natural to expect most things to work on the mobile device as well. With this premise, this FYP explores the possibility of having a native Android Application to be able to interact with the same database as the web version, but only focus on the necessary details. By specializing and selecting only the required details, the app will manage to remove much of unnecessary which are good to view on a computer screen but will prove overwhelming on a mobile device. The essential key is then to adapt the familiar web user interface (UI) and scale it down to a level appropriate on the mobile device, without too much fluff cluttering the screen, and only displaying the necessary data. Above all, the app should be a proof of concept that a full size web database system is capable of being scaled down to a native android level. In conclusion, an Android Application was created which allowed engineers and researchers to be able to look up information even when they are away from their workstations. The lightweight app features intuitive UI while displaying only the essential data.